2009
DOI: 10.1021/je900631y
|View full text |Cite
|
Sign up to set email alerts
|

Gas−Liquid Equilibrium Data for Sulfur Dioxide + Nitrogen in Diethylene Glycol + Water at 298.15 K and 123.15 kPa

Abstract: Isothermal gas-liquid equilibrium (GLE) data have been measured for the system diethylene glycol (DEG) (1) + water (2) + SO 2 (3) + N 2 (4) at 298.15 K and 123.15 kPa and SO 2 partial pressures in the range of (0.7 to 100) Pa. Measurements were carried out by a saturation method using a glass absorption apparatus, which was controlled at constant temperatures by a thermostatic circulation bath with a Beckmann thermometer. The GLE compositions were obtained with relative uncertainties within ( 0.6 % for SO 2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…However, the density and viscosity of PGME was lower than the other four alcohols, and the absorption capacity was stronger by comparing the values of Henry's constants. According to the literatures, 32,35 the dissolving of SO 2 in alcohol was due to the hydrogen bond and charge-transfer, which demonstrated that the charge-transfer may be easily between the alcohol-containing methoxy group and SO 2 . That is to say, there may be more free of alcohol hydroxyl than other alcohol and derivatives in PGME due to the weekly intermolecular hydrogen bond, which indicated the hydrogen bond is easily between free alcohol hydroxyls in PGME and SO 2 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the density and viscosity of PGME was lower than the other four alcohols, and the absorption capacity was stronger by comparing the values of Henry's constants. According to the literatures, 32,35 the dissolving of SO 2 in alcohol was due to the hydrogen bond and charge-transfer, which demonstrated that the charge-transfer may be easily between the alcohol-containing methoxy group and SO 2 . That is to say, there may be more free of alcohol hydroxyl than other alcohol and derivatives in PGME due to the weekly intermolecular hydrogen bond, which indicated the hydrogen bond is easily between free alcohol hydroxyls in PGME and SO 2 .…”
Section: Resultsmentioning
confidence: 98%
“…Henry’s constant and density and viscosity of five pure alcohol and alcohol derivatives including EG, DEG, TEG, PEG 300, and PGME are listed in Table . …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the equilibrium calculation, the S(IV) mainly exists in the forms of HSO 3 − and SO 2 in this pH range, and as the pH value decreases, the proportion of SO 2 increases. 26,34 An increase in the concen-tration of SO 2 in liquid phase reduces the rate of absorption of SO 2 . The absorption of NO x gases into the liquid phase is more complex than the absorption of SO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Especially, organic solvents used as absorbents had been identified as an option among the regenerative processes because regeneration can be carried out by pressure reduction, temperature increase, and use of a carrier gas. Considering all of these, the aqueous ethylene glycol and its similar compound solutions were paid great attention for several years because of its favorable properties, such as low vapor pressure, high chemical stability, and low melting point. On the other hand, ethylene glycol and its similar compounds present native hydrogen bonding sites for solubility of dilute SO 2 so that the potential desorption characters are presented in regenerative processes of desulfurizing solutions dissolving SO 2 .…”
Section: Introductionmentioning
confidence: 99%